Development of cost-effective media for the culture of Chilo partellus larvicide in Kenya - Anyika, D.; Boga, Hamadi I.; Mwirichia, Romano K. (Academic Journals, 2013)
Stem borers (Chilo partellus) are important field insect pests of maize (Zea mays L.) and sorghum (Sorghum bicolor L.) in Africa. They account for more than 30% yield losses depending on the composition of the pest community. C. partellus larvicide like Bacillus thuringiensis have been widely and effectively used in C. partellus control programs, but the industrial production of theses bacilli is expensive. Here we have attempted to develop three cost-effective media, based on legumes, potato, and whey. Growth and production of the insecticidal proteins from these bacteria were satisfactory; protein concentration yields of 27.60 mg/ml, spore counts of 5.60 × 108 CFU/ ml and first-instar Chilo partellus larvicidal activity (LC50) of 78 μg/l were obtained with a 72 h culture of this bacterium. Therefore, this investigation suggests that legume, potato and whey-based culture media are more economical and effective for the industrial production of B. thuringiensis insecticidal crystal proteins.
DOI: 10.5897/IJBMBR12.011
Keywords: Bacillus thuringiensis; larvicidal; Chilo partellus; insecticidal crystal proteins; LC50; optical density; sulphate polyacrylamide gel electrophoresis (SDS-PAGE); spore counts